2006
DOI: 10.1117/12.644790
|View full text |Cite
|
Sign up to set email alerts
|

Detection of potential osteoarthritis biomarkers using surface enhanced Raman spectroscopy in the near-infrared

Abstract: A novel application of surface-enhanced Raman spectroscopy (SERS) for in-vitro osteoarthritis (OA) biomarker detection is described. Hyaluronic acid (HA) is a potential OA biomarker and synovial fluid levels of HA have been correlated with progression of joint space narrowing. However, current immunoassay and chromatographic methods that identify HA in synovial fluid are cumbersome and often require sophisticated instrumentation. Raman spectroscopy may be an alternative to these analytical methods, providing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…As an important component of SF, HA has attracted the attention of researchers. Mandair et al [ 116 ] found that SERS could greatly enhance the signal intensity of HA, such that the minimum detectable concentration could be as low as 0.5 mg/mL. At the same time, effective protein removal techniques, including the trichloroacetic acid precipitation method, centrifugal method, and droplet deposition method, can effectively remove the influence of protein on Raman spectrum to observe HA more clearly.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…As an important component of SF, HA has attracted the attention of researchers. Mandair et al [ 116 ] found that SERS could greatly enhance the signal intensity of HA, such that the minimum detectable concentration could be as low as 0.5 mg/mL. At the same time, effective protein removal techniques, including the trichloroacetic acid precipitation method, centrifugal method, and droplet deposition method, can effectively remove the influence of protein on Raman spectrum to observe HA more clearly.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Quantitative chemical methods described in the literature to measure HA concentration include normal phase, reverse-phase ion-pair, and anion-exchange chromatography utilizing ultraviolet absorption and chemiluminescence, 17 high-performance liquid chromatography (HPLC) with fluorometric detection, 17 and surface-enhanced Raman spectroscopy. 18 , 19 Qualitative methods to image HA in tissues or on surfaces are primarily microscopy-based, notably optical and confocal microscopies. 20 22 Because HA is a multinegatively charged biopolymer, it binds cationic dyes, among them alcian blue (AB) 22 , 23 and Stains-All (E9379; Sigma-Aldrich Co, St Louis, MO, USA).…”
Section: Introductionmentioning
confidence: 99%
“…32,33 We demonstrated that SERS could detect HA drops at clinically relevant concentrations (0.125-3 mg/ml) that were undetected when spotted onto fused silica or non-enhancing gold surfaces. 34,35 Early experiments indicated that both drop shape and SERS spectra taken of the droplet were dependent upon HA concentration. 34 In this study, we examined the combined effects of drop thickness and shape, and polymer conformation on SERS spectra of hyaluronic acid drops dried onto a SERS-active surface.…”
Section: Introductionmentioning
confidence: 99%